The Difference a Justice May Make: Remarks at the Symposium for Justice Ruth Bader Ginsburg - Baer, Susanne (Columbia Journal of Gender and Law, 2012)
What have courts done to women? What can courts do for women? And what does it mean to do something for women without being paternalistic, or, eventually, maternalistic, which may be just as bad? These are questions Justice Ginsburg provided to inspire this symposium. Before I address them directly, we need to tackle some remarks on widespread assumptions that govern expectations around here, namely, expectations of, or attributions to, women on the bench. The key question is, then: What is it that makes a difference, regarding an individual justice or judge, at a court? In the German Federal Constitutional Court, there are two women in the First Senate, out of five female justices on the Court as a whole, who work with eleven men. Does this make a difference? What happened when one woman worked with seven men in one Senate, sometimes mocked as Snow White with the seven dwarfs, a rather discomforting comment for the men? Many believe biology matters, with more or less explicit reference to assumptions about femininity. What exactly is “this” that may indeed differ – the being female, being feminine, being male, or the masculinity of courts? Digging deeper, one may also want to ask whether this is too narrow a question.